Kaposiform Lymphangiomatosis in a Male Adolescent: A Clinical Challenge and the Role of Genetics - Joana Pereira-Nunes MD; Miguel Madureira MD; Alexandra Dinis MD; Helena Barroca MD; Jorge Lima Msc; Maria do Bom-Sucesso MD (SAGE Publishing, 2023)
Kaposiform lymphangiomatosis (KLA) is a rare and aggressive generalized lymphatic anomaly (GLA), with distinctive clinical, radiology, morphologic, and genetic features. It does not have a current standard treatment and presents poor overall prognosis. Somatic mutations in the RAS pathway were reported as the likely driver for the majority of patients. We report a case of a 17-year-old male adolescent who was referred to the emergency department due to a severe anemia. Laboratory workup confirmed the anemia and revealed coagulation factor consumption and fibrinolysis. Chest-abdomen-pelvis computed tomography revealed an extensive cervical, mediastinal, abdominal and retroperitoneal "hematoma." During admission, progressive pancytopenia, and disseminated intravascular coagulation were observed, and the hypothesis of a tumor/neoplastic etiology was considered. A thoracoscopy revealed a moderate hemorrhagic pleural effusion and a mediastinal mass resembling a "hemolymphangiomatosis" malformation, which was biopsied. Histology displayed a lymphatic-venous malformation. The patient was presented at the multidisciplinary Vascular Anomalies Center and, due to the complex vascular anomaly diagnosis, oral sirolimus monotherapy was initiated. Four years later, the patient remains clinically stable, with stability of the lesion's dimensions and characteristics. A p.Q61R variant in the NRAS gene [NM_002524.4: c.182A>G, p.(Gln61Arg)], with 5% allelic fraction and 1993x coverage was detected. In conjunction with clinical and pathological findings, it allowed KLA final diagnosis. This case reinforces the importance of a high index of clinical suspicion and highlights the need of referring these cases to referral to Vascular Anomalies Centers.